2018
DOI: 10.4108/eai.10-4-2018.155884
|View full text |Cite
|
Sign up to set email alerts
|

Security issues and Challenges in MANET-VANET-FANET: A Survey

Abstract: Security is one of the key important factors in ad hoc network due to the open wireless medium and dynamic topology of the network. MANET, VANET and FANET are type of ad hoc network and their applications are served the end users in real environment. VANET and FANET are next generation network and due to safety applications more attractions for end users in these networks. In this paper, we will provide the survey on security issues and challenges in the field of MANET, VANET and FANET. The successful implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Again, it can be shown that in (6), the parameter Distance represents the distance between the UAVs. However, it does not take into consideration the safety distance which should be respected by neighbor UAVs amongst themselves.…”
Section: ) Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, it can be shown that in (6), the parameter Distance represents the distance between the UAVs. However, it does not take into consideration the safety distance which should be respected by neighbor UAVs amongst themselves.…”
Section: ) Assumptionsmentioning
confidence: 99%
“…The associate editor coordinating the review of this manuscript and approving it for publication was Halil Ersin Soken . specific features and characteristics that make them different from MANETs and VANETs namely, higher mobility, deployment in squad formation, and fast and frequent network topology changes [6]. Consequently, these features do affect the stability of UAVs and makes the design of routing protocols quite challenging [7].…”
Section: Introductionmentioning
confidence: 99%
“…The mobility, number of nodes, and the ad hoc nature pose a huge impact on the dissemination of an Emergency Message. The FANETs is a relatively new research area in which the Emergency Message is broadcast using the techniques that are designed for MANETs and VANETs 20 . The cluster‐based recursive algorithm in Reference 21 reduces the delay and delivery ratio while broadcasting an emergency message in the Vehicular ad hoc network.…”
Section: Related Workmentioning
confidence: 99%
“…Since the entire system is invariably based on VANETs, therefore all relevant security challenges of a VANET would be applicable to TDRS as well. An extensive survey, research and in-depth analysis about current security implementation on VANETs have recently been done in [13] and [14], the studies of which would greatly aid towards the development of strong security implementations of TDRS.…”
Section: Challenges Of Tdrsmentioning
confidence: 99%